Developing Beef Cattle Industry at Smallholders to Support Beef Self-Sufficiency - Widiati, Rini (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
More than 90% of local beef supply derived from smallholder farmers with a relatively slow in growth that could not meet national demand. Price of imported beef was lower than that of the local beef, thus price adjustment in farmers level was not profitable. The purpose of this study is to recommend alternative strategies to develop beef cattle industry under smallholdersâ farmers condition. Strategies to develop the beef cattle industry are (1) To provide agricultural markets in order to facilitate farmerâs access easily to get some production inputs; (2) To facilitate technology that can be applied by farmers to increase cattle productions, hence improving farmersâ welfare; (3) To create a profitable market for animal produced by farmers; and (4) To establish subsystem of financing institutions at the village level to finance farmerâs cattle business. The inter-relationship among those strategies is needed to harmonize the implementation, supported by operational government policy. Key words: Industry, beef cattle, beef self-sufficiency